Oral Health-Related Knowledge, Attitudes and Behaviours of Arab Dental Students: Multi-National Cross-Sectional Study and Literature Analysis 2000-2020 - Riad, Abanoub; Al-Khanati, Nuraldeen Maher; Issa, Julien; Zenati, Mazen; Abdesslem, Nèziha Ben; Attia, Sameh; Krsek, Martin (International journal of environmental research and public health, 2022)
Dental students are the future leaders of oral health in their respective communities; therefore, their oral health-related attitudes and behaviours are of practical value for primary disease prevention. The present study aimed to evaluate oral health-related knowledge, attitudes, and behaviours of dental students in Arab countries and explore the potential sociodemographic predictors of their oral health outcomes. A multi-centre, cross-sectional study was conducted during the academic year 2019/2020 in three Arab countries: Lebanon, Syria, and Tunisia. The study used a validated Arabic version of the Hiroshima University Dental Behavioural Inventory (HU-DBI) composed of original twenty items that assess the level of oral health-related knowledge, attitudes, and behaviours, and four additional dichotomous items related to tobacco smoking, alcohol drinking, problematic internet use, and regular dental check-up The HU-DBI score ranges between 0 and 12. A total of 1430 students took part in this study, out of which 60.8% were females, 57.8% were enrolled in clinical years, 24.5% were tobacco smokers, 7.2% were alcohol drinkers, and 87% reported internet addiction. The mean HU-DBI score was 6.31 ± 1.84, with Lebanon having the highest score (6.67 ± 1.83), followed by Syria (6.38 ± 1.83) and Tunisia (6.05 ± 1.83). Clinical students (6.78 ± 1.70) had higher HU-DBI scores than their preclinical peers (5.97 ± 1.86). The year-over-year analysis revealed that dental public health and preventive dentistry courses had significantly and positively impacted the undergraduate students' knowledge, attitudes, and behaviours. The gender-based differences were not statistically significant, with a modest trend favouring males, especially oral health behaviours. Tobacco smoking, alcohol drinking, and problematic internet use were associated with lower HU-DBI scores. In the Arab world, the economic rank of the country where the dental students live/study was weakly correlated with the students' mean HU-DBI score.
Keywords: Arabs; Cross-Sectional Studies; Health Behavior; Male; practice; studenti stomatologie; Students, Dental; Health Knowledge, Attitudes, Practice; oral health; zdravé chování; Arab Countries; oral hygiene; attitudes; Oral Hygiene; mužské pohlaví; orální hygiena; health knowledge; orální zdraví; průzkumy a dotazníky; Lebanon; Hiroshima University Dental Behavioural Inventory—HU-DBI; Oral Health; Syria; lidé; ženské pohlaví; zdraví - znalosti, postoje, praxe; Humans; dental students; Arabové; dental education; průřezové studie; Tunisia; Libanon; Female; Surveys and Questionnaires